DEVELOPMENT AND VALIDATION OF A SUNDANESE LOCAL WISDOM BASED ISLAMIC RELIGIOUS EDUCATION MODULE FOR STRENGTHENING MORAL CHARACTER IN ELEMENTARY SCHOOL STUDENTS - Fitri Nurlatifah Azzahra; Habibah Nur Azizah; Taufik Hamdani; Maslani Maslani (SOSIOEDUKASI, 2025)
IIslamic Religious Education (PAI) in elementary schools frequently relies on standardized and text-based teaching materials that inadequately reflect students’ socio-cultural contexts, thereby limiting the internalization of moral values. This study aims to develop and evaluate a PAI teaching module on moral education integrated with Sundanese local wisdom—Silih Asah, Silih Asih, and Silih Asuh—and to examine its validity, practicality, and effectiveness. Employing a Research and Development (R&D) design, this study applied the ADDIE model comprising analysis, design, development, implementation, and evaluation stages. The module was tested with Grade V students at an Islamic elementary school in West Java. Data were collected through expert validation instruments, student response questionnaires, and pre-test and post-test assessments. The results indicate that the module achieved a high level of validity (90%), was categorized as very practical based on student responses (89.3%), and demonstrated high effectiveness in improving learning outcomes, with an average N-Gain score of 0.71 and a statistically significant improvement (p < 0.05). These findings suggest that integrating local cultural wisdom into PAI instructional materials effectively enhances students’ moral understanding and character formation. The developed module is therefore feasible as a contextual learning resource aligned with the Merdeka Curriculum and the Pancasila Student Profile.